CATARACT SURGERY AND DRY EYE DISEASE: A SYSTEMATIC REVIEW - Emir Hassan, Fauzan; Azhari, Ririn; Adenita, Qoshrina; Syarfina, Afdila; Ananda, Astrid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Dry eye disease after cataract surgery is associated with various risk factors, while causing a wide range of heterogeneous symptoms including decreased quality of vision.  Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up to date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.  Result: In the PubMed database, the results of our search brought up 385 articles, whereas the results of our search on SagePub brought up 56 articles. The results of the search conducted for the last year of 2013 yielded a total 27 articles for PubMed and 21 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria.  Conclusion:  This study comprehensively analyzed prevalence and characteristics after cataract surgery. It presents a concise and up to date description of the risk factors, prevention, and treatments. Our findings contribute to generating increased awareness among physicians, researchers, and the general population regarding after cataract surgery and encourage the development of effective preventative and treatment strategies.